What's new in the research on agricultural entrepreneurship? - Dias, Cláudia S. L. (2019)
Despite the mainstream entrepreneurship research had neglected the agricultural sector, this scenario seems to have changed in the last years with the study of new and diverse phenomena in several countries around the world. This study aims to analyse the state-of-the-art on agricultural entrepreneurship through a systematic literature review and applying the co-words bibliometric technique. The articles reviewed were obtained from the Scopus database, covering journals from all subject areas. The results allowed to identify three main approaches: i) Entrepreneurial Skills and Behaviour, ii) Entrepreneurial Strategies, and iii) Community and Entrepreneurial Activity. Based on this classification, the study shows that the Entrepreneurial Skills and Behaviour are examined essentially in developing countries, focusing on the assessment of entrepreneurship programmes, oriented not only to agricultural students in higher education institutes but also to women and young farmers. Entrepreneurial Strategies of farmers are analysed mainly in developed countries, although it can be based in the diversification of agricultural and non-agricultural businesses, innovation or market channels, depending considerably on factors such as country, type of product and size. Finally, the Community and Entrepreneurial Activity focuses essentially on the impacts of food production in communities of developed countries, highlighting the social entrepreneurship initiatives at urban agriculture.